2023
DOI: 10.1002/adfm.202303254
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Bacteria/MOF Hybrids Can Achieve Targeted Synergistic Chemotherapy and Chemodynamic Therapy against Breast Tumors

Abstract: The hypoxic tumor microenvironment (TME) significantly affects cancer treatment. Conventional chemotherapeutic agents cannot effectively target hypoxic tumor tissue, which decreases efficacy and results in severe toxic side effects. To alleviate this problem, a self‐driving biomotor is developed by functionalizing MCDP nanoparticles containing calcium peroxide and doxorubicin (DOX) loaded onto polydopamine‐coated metal–organic frameworks(MOF), with the anaerobic Bifidobacterium infantis (Bif) for synergistic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 63 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Fu S et al successfully developed a series of feasible strategies for the targeted delivery of chemotherapeutic drugs to the interior hypoxic areas of solid tumor tissue in virtue of the inherent-targeting ability of the anaerobic Bifidobacterium infantis (B. infantis, Bif), thus potentially improving efficacy and alleviate toxic side effects. [167][168][169][170] For instance, a Bifbased biohybrid (Bif@PDA-PTX-NPs) was designed to deliver polydopamine (PDA)-coated paclitaxel NPs (PTX-NPs) to tumor tissues, which realized the growth inhibition of A549 xenografts in nude mice, and the survival prolongation of the tumor-bearing mice without any systemic or localized toxicity, providing a new therapeutic strategy for targeted chemotherapy to solid tumors 167 (Figure 1).…”
Section: Synergistic Bacteria-mediated Chemotherapymentioning
confidence: 99%
“…Fu S et al successfully developed a series of feasible strategies for the targeted delivery of chemotherapeutic drugs to the interior hypoxic areas of solid tumor tissue in virtue of the inherent-targeting ability of the anaerobic Bifidobacterium infantis (B. infantis, Bif), thus potentially improving efficacy and alleviate toxic side effects. [167][168][169][170] For instance, a Bifbased biohybrid (Bif@PDA-PTX-NPs) was designed to deliver polydopamine (PDA)-coated paclitaxel NPs (PTX-NPs) to tumor tissues, which realized the growth inhibition of A549 xenografts in nude mice, and the survival prolongation of the tumor-bearing mice without any systemic or localized toxicity, providing a new therapeutic strategy for targeted chemotherapy to solid tumors 167 (Figure 1).…”
Section: Synergistic Bacteria-mediated Chemotherapymentioning
confidence: 99%
“…Recently, different research groups have reported pioneering examples of MOFs themselves as efficient nanocatalysts and theranostic agents. 122–132 According to the function roles of MOFs in the construction of CDT agents, two categories of MOF-based nanocatalysts will be summarized in this part. The first section will elaborate on MOFs as nanocarriers of CDT agents by in situ hybridization or post-synthetic modification.…”
Section: Strategies To Construct Hybrid Cdt Agents Based On Diverse N...mentioning
confidence: 99%
“…15A), wherein the DOX and the PVP-functionalized CaO 2 NPs were loaded on the Fe-MOF with PDA coating and finally attached to the surface of anaerobic B. infantis . 123 Due to the inherent targeting ability of B. infantis bacteria, this biohybrid could actively accumulate in the hypoxic tumor region and selectively release DOX, CaO 2 , and Fe 2+ from the Fe-MOF by pH-induced PDA degradation. CaO 2 readily decomposes in the acidic TME to release Ca 2+ and H 2 O 2 , which was converted into abundant ˙OH for improved CDT by Fe 2+ -initiated Fenton reaction and GSH depletion.…”
Section: Strategies To Construct Hybrid Cdt Agents Based On Diverse N...mentioning
confidence: 99%
“…Osteosarcoma (OS) is the most common primary malignant bone tumor affecting children and adolescents. The traditional therapy for OS is surgical resection combined with chemotherapy or radiotherapy. However, chemotherapy is generally accompanied by severe side-effects, poor prognosis, and poor survival. , Moreover, tumor hypoxia, as one of the characteristics of the tumor microenvironment (TME), severely limited the therapeutic efficiency oxygen-related tumor therapies, such as radiotherapy and photodynamic therapy. Tumor hypoxia also often associated with tumor invasion, metastasis, and recurrence. , Currently, nanomaterial-based drug delivery systems have been developed to solve these problems. Such nanodrug delivery systems are able to integrate various functions of targeting, therapeutics, and imaging within a single platform. Furthermore, oxygen-carrying nanoplatforms were employed as oxygen shuttles to deliver oxygen and relieve tumor hypoxia. , Despite these advantages, these materials are intensively stuck with complex synthetic procedures, high cost, and unexpected toxicity, limiting their use in biological applications. Therefore, there is an urgent need for new strategies for OS treatment with fewer side-effects, higher efficacy, lower cost, and multifunctionality.…”
Section: Introductionmentioning
confidence: 99%